184 Placental Mesenchymal Stromal Cells Seeded on an Extracellular Matrix Scaffold Improve Motor Function Recovery After Acute Spinal Cord Injury. (1st April 2022) - Kulubya, Edwin; Jackson, Jordan; Bhaskara, Mounika; Kumar, Priya; Pivetti, Christopher; Avallone, Samantha; Paxton, Zachary; Reed, Camille; Mor, Sirjan; Wang, Aijun; Farmer, Diana
Abstract : INTRODUCTION: Spinal cord injury (SCI) is a devasting disease associated with severe disability and no effective cure. SCI involves a primary traumatic injury followed by a secondary injury characterized by inflammation, ischemia, and formation of a glial scar. Cellular therapies aim to minimize the secondary injury by protecting the remaining cells and promoting neuronal and glial regeneration. We have shown placental mesenchymal stromal cells (PMSCs) applied in utero improve ambulatory function and preserve motor neurons in an ovine model of spina bifida and have begun a first-in-human clinical trial for fetal spina bifida. METHODS: Female Sprague Dawley rats were given a right C5 hemi-contusion injury using an RWD Precise Impactor and 8 rats served as sham surgery controls. Immediately following injury, rats were treated with an ECM only (n = 9) or an ECM seeded with 3 x 105 PMSCs (PMSC-ECM, n = 11). Weekly motor function testing included Irvine, Beatties, and Bresnahan (IBB) Forelimb Recovery Scale testing by blinded reviewers. After 8 weeks, rats were euthanized, and tissue collected for histology. RESULTS: Four second trimester PMSC cell lines were evaluated with our established anti-apoptotic neuroprotection assay and a single cell line was chosen based on increased neurite outgrowths. Within the PMSC-ECM group, rats had statistically significant improvement in their IBB scores between week 1 and week 8 (p = 0.002) compared to ECM only group, where rats did not show improvement (p = 0.063). When comparing IBB scores between groups at week 8, PMSC-ECM rats had a significantly higher IBB score compared to ECM only rats (p = 0.015). CONCLUSION: PMSCs improved motor function recovery in a rodent model of SCI. Further studies include immunohistochemical analysis and delivering PMSC derived exosomes as a cell-free treatment.